UX design for trustworthy ai: five principles and product patterns for teams - Gnatovych, V. (ТОВ «Видавництво Ліра-К», 2025)
This thesis explores UX design strategies for fostering trust in AI systems through real-world applications across healthcare, finance, and content moderation. It introduces a framework of five trust-enabling principles derived from cross- sector product implementations and academic literature (2018–2025). Designed from a UX and product lens, the framework helps teams operationalize explainability, user control, and system transparency in AI-powered experiences.
Keywords: UX; design